Seychelles : 2013 Article IV Consultation, Seventh Review Under the Extended Arrangement and Request for Modification of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2013)
This staff report discusses Seychelles 2013 Article IV Consultation, Seventh Review Under the Extended Arrangement and Request for Modification of Performance Criterion. The repayment of domestic debt, a preference for foreign financing, and shallow domestic financial markets have resulted in significant structural rupee liquidity in the banking system. Tourism has been the main driver of growth, but there is a tension with the number of tourists the islands can absorb. Despite the challenging global environment, tourist arrivals have grown strongly, with diversification toward nontraditional markets more than offsetting stalling European arrivals. The Seychellois rupee is broadly in line with medium-term fundamentals, and tourism remains competitive among peers.